Real-time change of nitric oxide in rat hippocampal slices and astrocytic glutathione release via glutamate-dependent pathways - Frade, João Gonçalo Leal de Oliveira e Silva (2008)
Tese de doutoramento em Bioquímica (Toxicologia Bioquímica) apresentada à Fac. de Ciências e Tecnologia da Univ. de Coimbra